2020
DOI: 10.1002/nse2.20020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding online homework assignments to a small introductory physical geology class

Abstract: Online homework (OLH) assignments were added to the Introduction to Physical Geology class at Dickinson State University in the fall semester of 2014. Anticipated advantages included timely feedback and opportunities for students to correct mistakes made during homework completion. The same instructor taught all lecture and laboratory sections over the course of the study, and student performance was compared for the 3 years prior to adopting the OLH and the 3 years after. Following adoption of the OLH, the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Several studies have shown that well-developed online activities can benefit student learning (Mayer & Moreno, 2002;Chang and Wang, 2009;Brevik, 2020;Vasiliadou, 2020). Hegerfeld-Baker 2013found that the virtual laboratories available on the VL website increased interest in agricultural science careers among students who did not have access to traditional laboratory science in high school.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that well-developed online activities can benefit student learning (Mayer & Moreno, 2002;Chang and Wang, 2009;Brevik, 2020;Vasiliadou, 2020). Hegerfeld-Baker 2013found that the virtual laboratories available on the VL website increased interest in agricultural science careers among students who did not have access to traditional laboratory science in high school.…”
Section: Discussionmentioning
confidence: 99%
“…Online education began in the 1980s and grew rapidly with the development of the World Wide Web in the 1990s (Harasim, 2000), offering several possibilities for education that did not exist just a few years before. Well‐developed online activities have been shown to enhance student learning in the sciences (Brevik, 2020; Chang & Wang, 2009; Mayer & Moreno, 2002; Vasiliadou, 2020), including soil science (Hegerfeld‐Baker, 2013; King et al., 2014; Ulery et al., 2020). For example, the use of computer graphics and animated videos has been shown to be effective at helping introductory soil science students understand concepts such as cation exchange capacity and sorption (Ulery et al., 2020).…”
Section: Place Of Soil Science Within Postsecondary Educationmentioning
confidence: 99%
“…Şahin ve Kılıç'ın (2021a) "Demokratik Yaşama Dayalı Öğrenme Modeli"nin etkililiğini belirlemek için yaptıkları çalışmada da öğrencilerin modelde yer alan bireysel çalışmaları gerekli ve etkili buldukları sonucuna ulaşılmıştır. Literatürde de ders öncesi yapılan bireysel çalışmaların öğrencilerin öğrenmelerini olumlu etkilediğini, derse aktif katılımlarını ve başarılarını artırdığını gösteren çok sayıda çalışma mevcuttur (Brevik, 2020;Dolean ve Lervag, 2020;Frydenberg, 2012;Garcia, 2018;Herold, Lynch, Ramnath ve Ramanathan, 2012;Ökmen, 2020;Ronkainen, 2015;Talbert, 2012;Yamane, 2006).…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified